Penerapan Intervensi Self-Management Berbasis Whatsapp (Wa) Pada Pasien Gagal Ginjal Kronik (Ggk) Yang Menjalani Hemodialisis (Hd) Di Rumah Sakit Pku Muhammadiyah Gamping: Laporan Kasus - Fadila Strinareswara; Ambar Relawati; Indri Setiyawati (STIKes Ibnu Sina Ajibarang, 2024)
Hemodialysis (HD) is the most common kidney replacement therapy in the world. HD will affect changes in the patient's lifestyle. WA-based self-management program as one of the interventions in managing HD patients. This study aims to determine the effectiveness of implementing WA-based self-management interventions in CKD patients undergoing HD. This study is a case report using a nursing care approach with HDMI questionnaires as pretest and posttest. The results of this study showed that there was an increase in the average HDMI score by 9 points and decrease the average of IDWG in respondent 1 by 0.19 kg, while respondent 2 by 1.67 kg. Conclusion: the application of WA-based self-management intervention is effective in increasing self-management scores. However, this program less effective to reduce IDWG according to expected target in patients undergoing HD at PKU Muhammadiyah Gamping.